Regulation of intestinal flora by Suaeda salsa extract ameliorates hyperglycemia in a mouse model of type 2 diabetes mellitus - Yin, Xuemei; Sui, Yinzi; Chu, Zhengyan; Han, Suqing; Ge, Xiaodong; Liu, Tingting; Zeng, Feng; Chen, Ligen; Shao, Rong; Xu, Wei (Frontiers in Nutrition, 2024)
Type 2 diabetes mellitus (T2DM) often leads to elevated blood glucose levels and lipid metabolism disorder, which is generally accompanied by dysbiosis of gut microbiota and metabolic dysfunction. In this study, a mouse model of T2DM was established by feeding a high-fat/sucrose diet combined with injecting a low dose of streptozotocin. The aim of this study was to analyze the regulatory effect of Suaeda salsa extract (SSE) on T2DM and its effect on the intestinal flora of mice. The results showed that SSE could significantly improve the body weight, fasting blood glucose (FBG), area under the curve (AUC) of the oral glucose tolerance test (OGTT), glycosylated serum protein (GSP) and islet function index. Moreover, 4-week body weight, FBG, AUC of OGTT, GSP, as well as intestinal acetic and butyric acid were significantly better in the SSE-L than in the MET group (p < 0.05). In addition, it was also found that the potential hypoglycemic mechanism of SSE was related to the expression of Akt serine/threonine kinase (AKT-1) and glucose transporter-2 (GLUT-2) genes. Compared with the model group, SSE intervention significantly increased the abundance of probiotics, such as Soleaferrea, Alloprevotella, Lactobacillus and Faecalibaculum, while decreasing the relative abundance of harmful bacteria, such as Phocaeicola and Bilophila. Analysis of the correlation among intestinal microbiota, short chain fatty acids (SCFAs) and the hypoglycemic index showed that Dwaynesavagella was significantly correlated with acetic, propionic and butyric acid, as well as all the diabetes-related indexes analyzed in this study. Thus, this taxon can potentially be used as a microbiological marker of type 2 diabetes. Taken together, these findings demonstrate that SSE can alleviate T2DM and its complications by improving glycemia-related indicators and modulating the structure of intestinal flora.